Psychosocial risks among migrant workers in the Middle East construction sector - Hassan, Haitham (2020)
Background: The Middle East has witnessed an unprecedented construction boom in recent years supported by a massive migrant workforce. The working conditions of this workforce are generally recognized as poor. Few researchers have examined health and safety and their possible relations with the psychosocial working conditions of this workforce. A paucity of knowledge exists on the occupational risks to health and safety in this population, and this is particularly the case for risks arising from the psychosocial work environment. Added knowledge in this domain could usefully inform risk reduction activities concerning modification to the design, organization, and management of work as a means to protect and promote workers’ health and safety.